Symbiotic nitrogen-fixation and yield of soybean inoculated with acid-tolerant rhizobia strains following soil amendments under low soil pH conditions of Rwanda - Nzeyimana, F.; Onwonga, R.N.; Ayuke, F.; Chemining'wa, G.N.; Nabahungu, N.L.; Sylvere, S.N.; Josiane, U.K.N. (2025)
Soil acidity is a limiting factor in legume system during plant growth and microsymbionts process. The aim of this work was to identify and document acid tolerant rhizobium strains and their response to soybean grain yield under low pH. Ninety-one rhizobia isolates were collected from two provinces (Eastern and southern) of Rwanda based on soil acidity in the two regions. Symbiotic nitrogen fixation and yield were determined for three soybean varieties (PK6, SB24 and Sc Squire) inoculated with three acid-tolerant rhizobia strains (BB18S, BB64S and SB88E) across two sites with contrasting soil pH conditions. Interaction of soybean variety and soil amendments significantly revealed differences (p-value≤0.012), where organic manure increased the number of nodules for two promiscuous varieties (SB24 and Sc Squire). Non-inoculated soybean control produced low N-fixed compared to all inoculated treatments, with high performance recorded for SB88E strain. The total dry matter biomass generated high grain yield, and this resulted from N-fixation due to the interaction between the acid tolerant rhizobia strains, soybean variety and application of N starter, P and K. Interaction of soybean variety and soil amendments revealed significant differences (p-value≤0.012), with organic manure application increasing the number of nodules for two the promiscuous varieties (SB24 and Sc Squire). The biomass production generated high (p=000) grain yield by significantly (p=000) increasing the pod yields. The N-fixing efficiency of the strains was affected by N, P, and K application and legume isolates, and the grain yield increased when organic manure was applied on PK6 at the site with low pH and increased when lime and organic manure were applied on SB24 and Sc Squire. The study offers a technical solution for addressing soil acidity, nutrient availability, and enhancing soybean yield in Eastern and Southern Rwanda and similar agroecological regions.